2017
DOI: 10.1038/s41598-017-01561-2
|View full text |Cite
|
Sign up to set email alerts
|

Kai-Xin-San series formulae alleviate depressive-like behaviors on chronic mild stressed mice via regulating neurotrophic factor system on hippocampus

Abstract: Kai-xin-san (KXS) is a famous Chinese medicinal formula applied for treating stress-related psychiatric diseases with the symptoms such as depression, forgetfulness and dizziness. In clinic, the composition ratio of KXS is always varied and KXS series formulae are created. Here, we aim to compare the anti-depressive effect of different ratios of KXS and reveal its action mechanism on regulation of neurotrophic factor system. Firstly, daily intra-gastric administration of chemically standardized extracts of KXS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
1
28
1
Order By: Relevance
“…Moreover, it promoted neurogenesis via inducing the expression of synaptotagmin and dendritic spine density in cultured neurons and increased neurotrophins in astrocytes which might concern the regulation of Erk1/2 and CREB phosphorylation . In further studies of Zhu et al, KXS was confirmed to promote expressions of neurotrophic factors and TrkB receptors. By combining qPCR, Western blotting and constituent identification analysis, ginsenoside Rg1 and Rb1 may be active compounds in this component that increase NGF and BDNF expression by activating cAMP‐dependent signalling pathway and stimulating neurotrophic factor synthase .…”
Section: Antidepressant Effects Of Representative Panax Ginseng Herbamentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, it promoted neurogenesis via inducing the expression of synaptotagmin and dendritic spine density in cultured neurons and increased neurotrophins in astrocytes which might concern the regulation of Erk1/2 and CREB phosphorylation . In further studies of Zhu et al, KXS was confirmed to promote expressions of neurotrophic factors and TrkB receptors. By combining qPCR, Western blotting and constituent identification analysis, ginsenoside Rg1 and Rb1 may be active compounds in this component that increase NGF and BDNF expression by activating cAMP‐dependent signalling pathway and stimulating neurotrophic factor synthase .…”
Section: Antidepressant Effects Of Representative Panax Ginseng Herbamentioning
confidence: 86%
“…108 It is possible that Rg3 could be used to treat these disorders based on the regulation of BDNF expression, which needs to be further studied. 61 Increases the protein levels of BDNF, NGF and GDNF, as well as the mRNA expressions of Trk receptors [92][93][94] Promotes neurogenesis and synaptogenesis 92,95 Influences the inflammatory processes via reduction of COX-2, IL-2, IL-6, TNF-α levels and increase of IL-10, IFN-γ levels 97 SYG GTS, PTG GTS, PTG Modulates the levels of 5-HT, DA, NE and ACh 99 XD Bupleurum, Scutellaria, Panax ginseng, Pinellia, Ginger, Glycyrrhiza, Jujube…”
Section: Effec Ts Of Pana X G In S Eng On Other Cn S D Is E a S E Smentioning
confidence: 99%
“…Wolf ), Polygalae (Polygala tenuifolia Wild) and Acorus (Acorus tatarinowii rhizome) with dosage proportion of 3 : 3 : 2 : 2, has been used to treat amnesia for thousands of years in China. Indeed, KXS improves learning and memory in experimental AD studies and the mechanisms were correlated with multiple effects [5,6], including reduced Aβ toxicity, neuroprotection, and neurites regeneration improvement. Similarly, our previous studies demonstrated that KXS ameliorates neuron loss and cognitive dysfunction induced by Aβ in vivo [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ding-Zhi-Wan, a famous herbal formula of traditional Chinese medicine that was formerly reported in Chinese ancient book (Bei Ji Qian Jin Yao Fang) by Sun Simiao, has another name as Kai-Xin-San (KXS) in (Tai Ping Hui Min He Ji Ju Fang) [5]. Kai-Xin-San (KXS), a famous herbal formula of traditional Chinese medicine, consists of Radix Ginseng (Radix Ginseng C.A.…”
Section: Introductionmentioning
confidence: 99%
“…However, many deficiencies exist such as long medication cycle, serious toxic and side effects, poor medication compliance, repeated disease delay, etc., which can greatly affect the prognosis and clinical application of the disease [8]. TCM also has therapeutic effects on depression-related symptoms For example, Xiaoyaosan [9] is used to soothe liver, relieve depression and invigorate spleen; Kai-xin-san [10] is applied to invigorate qi, nourish heart and tranquilize mind; Chaihu Shugan San [11], etc. A meta-analysis result has shown that [12] Chaihu-longgu-muli decoction or combination of antidepressants is superior to antidepressants alone in the treatment of depression, which can significantly reduce the incidence of adverse reactions during medication.…”
Section: Introductionmentioning
confidence: 99%